METAPHOR IN LITERATURE. ANALYSIS OF THE TERM THROUGH NOVEL “ANIMAL FARM” BY GEORGE ORWELL. - Hoshimova, Mahfuza (Журнал иностранных языков и лингвистики, 2021)
The article touches upon metaphor and using it in literature, such as prose. As we know, the word is considered the most important tool in literature due to its importance to make the meaning of your work clearer and more impressive. This article is dedicated to using this term in one of different genres and finding out reasons or aim of writers to use metaphor in their work. So as to do analysis, “Animal farm” by George Orwell can be a good example as it is about animal at the farm. The novelty of the article is finding different metaphors in one work, and analyze what purpose from using.